Back Cover: Biomimetic RNA‐Silencing Nanocomplexes: Overcoming Multidrug Resistance in Cancer Cells (Angew. Chem. Int. Ed. 7/2014). Issue 7 (20th January 2014) - Wang, Zhongliang; Wang, Zhe; Liu, Dingbin; Yan, Xuefeng; Wang, Fu; Niu, Gang; Yang, Min; Chen, Xiaoyuan
<x xml:space="preserve">Abstract</x> Synthetic RISC‐mimic nanocomplexes for sequence‐specific gene silencing are demonstrated by X. Chen, M. Yang, et al. in their Communication on page 1997 ff. Owing to unusual cooperative interaction among the components, the nanocomplexes, which were designed to target multidrug resistance, are able to successfully restore the sensitivity of OVCAR8/ADR cells to Pgp‐transportable cytotoxic agents, and also exhibit resistance to enzymatic degradation, excellent target selectivity, and specific self‐delivery.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>